Between Tradition and Disruption: A Literature Review on the Role of Family Firm Dispositions in Navigating Digital Transformation - Ngadi Permana; Tanti Sugiharti (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2026)
This qualitative literature review examines how distinctive dispositional traits of family firms—such as socioemotional wealth, long-term orientation, and tradition—shape their engagement with digital transformation (DT). Drawing on recent empirical studies from 2007 to 2025, the review reveals that these dispositions serve as both barriers and enablers of digital change. While tradition and risk aversion can hinder radical innovation, they can also foster stability and purpose-driven digital adoption. The review highlights how family firms navigate paradoxes between continuity and innovation through strategic framing, intergenerational collaboration, and openness to external knowledge. Ultimately, family firm dispositions mediate digital transformation in complex, context-dependent ways, offering alternative, non-linear paths to innovation. This synthesis contributes to understanding how legacy and digitalization can be harmonized in family-owned businesses